Iran - Energy : Environment Review Policy Note - World Bank (Washington, DC, 2013)
This Policy Note is based on the Final Report of the Environmental Energy Review (EER), prepared over two years, with the full collaboration of the Government of Iran, and the assistance of international, and national consultants. The EER report comprises: an analysis of the current situation with regards to energy generation, and use; an evaluation of the growth prospects with regard to energy generation, and use; the identification of the environmental issues induced by the generation, and use of energy, and the cost estimates of damages; the evaluation of the extent of contribution to the climate-change phenomenon, through emission of greenhouse gases; the evaluation of the proposed mitigating measures for previously identified environmental problems; conclusions and recommendations; and, a proposal for an action plan. The emphasis of the EER is on air pollution, being the most extreme, visible sign of environmental damage, certainly in the large cities. The major source of air pollution is the energy sector, key to the Iranian economy, and, the main engine of future economic growth, though a principal cause of environmental pollution, and a major source of market distortion. The challenge therefore is to recommend the necessary policy reforms and sectoral measures that will substantially reduce damage costs, in the case that no reform or measures are introduced. In order to better define the options, and their impacts, a total of twelve scenarios were analyzed, characterized by a combination of four price reform scenarios, and three different sets of measures. Major conclusions from this analysis suggest rapid price reform, as a strategy for the environment, through a combination of price reform, plus appropriate sectoral measures. If price reform is delayed past 2009, then the country can improve its financial cash-flow by providing financial incentives to the efficient use of energy, and to the substitution of fuel-oil by natural gas, avoiding subsidies, and instead fund other environmental control measures, where the costs are not easily assigned to the polluter. The policy note also proposes an Action Plan to implement the main sectoral policies described above.